2013
DOI: 10.3126/njh.v9i1.8346
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension among Young Adults in the Shopping Malls of Kathmandu

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Reddy et al from Karnataka [22] also reported 7.2% prevalence of hypertension among 18 to 25 years young adults. Shakya et al [23] reported rather high prevalence of hypertension from the Mall attending young adults of Nepal. However, the socioeconomic consumption is associated with higher levels of blood pressure [27][28][29].…”
Section: Discussionmentioning
confidence: 98%
“…Reddy et al from Karnataka [22] also reported 7.2% prevalence of hypertension among 18 to 25 years young adults. Shakya et al [23] reported rather high prevalence of hypertension from the Mall attending young adults of Nepal. However, the socioeconomic consumption is associated with higher levels of blood pressure [27][28][29].…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of prehypertension in the present study is similar to the 30% prevalence reported from a study done among young adults in a shopping mall of Kathmandu, Nepal. 12 In a cross sectional study done in adults of 18 years and above living in Central Development region of Nepal, hypertensive subjects were found to be 22.4% and prehypertensive subjects were more than double the hypertensives (48%). 13 A systematic review and metaanalysis done in a large population of urban, suburban, and rural areas of Nepal found the prevalence of prehypertension to be 35.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The data is higher in compare to the 7th Report of the JNC on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure which stated it was approximately 30 percent 2 and is much less than a study of Dhulikhel that showed 69.9% of hypertensive were unaware of their hypertensive status 14 and almost similar (39.1%) to a study of city malls in Kathmandu that showed only 39.13%. 18 Out of 112 participants who have never checked BP in last 12 months, 24 (11.2%) have hypertension and did not know about their hypertensive state and who responded as they are hypertensive (163 participants), 100 (61.3%) had responded they are currently on allopathic medication. However medication history was collected on basis of the information provided by the participants without further verification.…”
mentioning
confidence: 99%